The Relationship Between Social Identity, Academic Achievement, And Sports Participation In Badminton: Literature Review - Muhammad Ishak (Journal of Sport Education, Coaching, and Health (JOCCA), 2026)
Social identity, academic achievement, and sport participation are important factors influencing the holistic development of student-athletes. In badminton, athletes are required not only to achieve optimal sporting performance but also to maintain academic responsibilities. However, studies examining the interrelationship among social identity, academic achievement, and badminton participation remain fragmented. Therefore, this literature review aimed to analyze the conceptual and empirical relationships among these three constructs and to develop an integrative understanding of their role in athlete development. This study employed a literature review design by synthesizing scientific publications from reputable databases, including Scopus, Web of Science, PubMed, ScienceDirect, ERIC, Google Scholar, SINTA, and Garuda. Articles published between 2015 and 2025 were screened using predefined inclusion and exclusion criteria. A total of 78 studies were initially identified, 60 articles were screened after duplicate removal, and 20 eligible studies were included in the final analysis. Data were analyzed using a thematic synthesis approach focusing on social identity, academic achievement, and sport participation. The findings revealed that 85% of the reviewed studies reported a positive relationship between social identity and sport participation, while 80% found that sport participation positively influenced academic achievement. Furthermore, 70% of studies indicated a direct relationship between social identity and academic achievement, and 65% demonstrated that social identity indirectly enhanced academic outcomes through increased sport participation. Social identity was found to strengthen motivation, commitment, resilience, social support, and self-regulation, which are essential for both sporting and academic success. In conclusion, social identity serves as a critical psychosocial mechanism linking badminton participation and academic achievement. Strengthening social identity within badminton environments may contribute to sustainable athlete participation, improved educational outcomes, and holistic athlete development.